Assessment of the Efficacy and Safety of BMS-820836 in Patients With Treatment-Resistant Major Depression: Results From 2 Randomized, Double-Blind Studies. Issue 4 (August 2015) - Bhagwagar, Zubin; Torbeyns, Anne; Hennicken, Delphine; Zheng, Ming; Dunlop, Boadie W.; Mathew, Sanjay J.; Khan, Arif; Weisler, Richard; Nelson, Craig; Shelton, Richard; Thase, Michael E.; Lane, Roger
Abstract : Abstract: Two phase 2B, randomized, double-blind studies assessed the efficacy and safety of fixed or flexible dose of triple monoamine uptake inhibitor BMS-820836 in patients with treatment-resistant depression to demonstrate whether switching to BMS-820836 was superior to the continuation of standard antidepressant treatment. Patients with a history of inadequate response to 1 to 3 adequate trials of antidepressant therapies were prospectively treated with duloxetine 60 mg/d for 8 weeks (CN162-006) or duloxetine 60 mg/d or escitalopram 20 mg/d for 7 weeks (CN162-007). Inadequate responders were randomized to continue their prospective phase treatment or switch to flexible-dose (0.5–2 mg/d; CN162-006) or fixed-dose (0.25, 0.5, 1, or 2 mg/d; CN162-007) BMS-820836 for 6 weeks. The primary end point in both studies was mean change in Montgomery-Åsberg Depression Rating Scale (MADRS) total score from randomization to study end point. BMS-820836 flexible (0.5–2 mg/d) or fixed dose of 1 mg/d or greater showed efficacy similar to the continuation of antidepressant treatment, with no statistically significant or clinically meaningful differences. In the CN162-006 study, the adjusted mean (SE) change in MADRS total score was −8.7 (0.661) and −8.1 (0.656) for BMS-820836 and duloxetine, respectively ( P = 0.526). In the CN162-007 study, the adjusted mean (SE) change in MADRS total score was −7.3 (0.830) and −6.6 (0.842) for BMS-820836 of 1 and 2 mg, respectively, and −6.9 (0.602) for the continuation group ( P = 0.910). Thus, BMS-820836 was well tolerated, with no evidence of dose-dependent discontinuations due to adverse events, but it failed to demonstrate superiority to the continuation of an existing antidepressant in patients with treatment-resistant depression. Abstract : Supplemental digital content is available in the text.